Computer Safety, Reliability, and Security : 34th International Conference, SAFECOMP 2015, Delft, The Netherlands, September 23-25, 2015, Proceedings - Koornneef, Floor; van Gulijk, Coen.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 34th International Conference on Computer Safety, Reliability, and Security, SAFECOMP 2015, held in Delft, The Netherlands, in September 2014. The 32 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 104 submissions. The papers are organized in topical sections on flight systems, automotive embedded systems, automotive software, error detection, medical safety cases, medical systems, architecture and testing, safety cases, security attacks, cyber security and integration, and programming and compiling.
Keywords: Logic design; Computer science; Software engineering; Computer security; Computer network architectures; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Software Engineering; Systems and Data Security; Computer Applications; Computer Systems Organization and Communication Networks